2022
DOI: 10.1001/jamanetworkopen.2022.15396
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Comorbidities, Clinical Outcomes, and Parathyroidectomy in Adults With Primary Hyperparathyroidism

Abstract: This cohort study examines the association of fractures, cardiovascular events, and mortality with untreated primary hyperparathyroidism and with surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
2
7
0
1
Order By: Relevance
“…A longitudinal cohort study of 3213 Danish patients with PHPT diagnosed from 1989 to 1999 with a median 6.1 years follow-up found no difference in the hazard of MI, hypertension, heart failure, arrhythmia, or stroke between patients treated with parathyroidectomy versus those managed nonoperatively after adjusting for age, sex, and history of each event prior to PHPT diagnosis 36 . A recently published population-based study of 16,374 patients with PHPT in Sweden showed a reduced risk of CV events in patients with PHPT who were treated with parathyroidectomy (HR: 0.84, 95% CI: 0.73–0.97), similar to our findings 37 . Long-term follow-up data from the 191-patient Scandinavian Investigation of Primary Hyperparathyroidism (SIPH) randomized controlled trial showed no statistically significant difference in the secondary outcome of CV events (HR: 0.81, 95% CI: 0.33–1.99) among adults with asymptomatic PHPT managed with parathyroidectomy versus nonoperatively, but this study was underpowered to detect differences in CV outcomes 38 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A longitudinal cohort study of 3213 Danish patients with PHPT diagnosed from 1989 to 1999 with a median 6.1 years follow-up found no difference in the hazard of MI, hypertension, heart failure, arrhythmia, or stroke between patients treated with parathyroidectomy versus those managed nonoperatively after adjusting for age, sex, and history of each event prior to PHPT diagnosis 36 . A recently published population-based study of 16,374 patients with PHPT in Sweden showed a reduced risk of CV events in patients with PHPT who were treated with parathyroidectomy (HR: 0.84, 95% CI: 0.73–0.97), similar to our findings 37 . Long-term follow-up data from the 191-patient Scandinavian Investigation of Primary Hyperparathyroidism (SIPH) randomized controlled trial showed no statistically significant difference in the secondary outcome of CV events (HR: 0.81, 95% CI: 0.33–1.99) among adults with asymptomatic PHPT managed with parathyroidectomy versus nonoperatively, but this study was underpowered to detect differences in CV outcomes 38 .…”
Section: Discussionsupporting
confidence: 89%
“…These prior studies suggested that surgical cure with parathyroidectomy would alter the CV risk profile of patients with PHPT and lead to improved CV outcomes, consistent with our findings. However, it is important to note that the CV benefits of parathyroidectomy in our study and the recent Swedish cohort study 37 were modest and most likely to be clinically meaningful on long-term follow-up (ie, 5–10 years following surgery), which may not be relevant to patients with limited life expectancy. It is possible that more nuanced, short-term CV benefits are experienced by patients with PHPT treated operatively but that these are not as evident in the current analysis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, the risk was reduced significantly for patients who had undergone a parathyroidectomy. This study brings to light the effect of PHPT on cardiovascular health and the benefit of parathyroidectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated increased mortality in severe PHPT, but the effect of asymptomatic PHPT on mortality and benefit of parathyroidectomy are controversial. An observational study of 16 374 patients with PHPT and 163 740 control patients indicated that those with PHPT had a higher risk of death (51.83 vs 30.95 per 1000 person-years) and parathyroidectomy reduced risk (hazard ratio, 0.59) . A smaller RCT of 191 patients reported no benefit of parathyroidectomy on mortality compared with observation at 10-year follow-up (25.3% vs 20.8%) …”
Section: Observations and Discussionmentioning
confidence: 99%